Implementasi Konvensi Hak Anak Di Kota Jakarta Utara (Studi Kasus: Pemenuhan Hak Asasi Manusia Perspektif Pendidikan Bagi Pelajar SMA) - Fanisyah Salsabila Octavianti (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
Every human being who lives by nature has basic rights within himself which are called Human Rights, including in the field of education. In this case, the requirement that the children's convention be enforced in Indonesia is to protect children and safeguard their rights to education, including in North Jakarta City. With the realization of a children's convention in North Jakarta City, it will be a good incentive for millennial generation children in this 4.0 industrial revolution era. This study aims to find a solutive solution to improve the fulfillment of human rights in an educational perspective for high school students in North Jakarta. The findings from the research are one form of solutive solution to increase human rights in the educational environment of North Jakarta City in the form of the right to attend education for every community which has broad implications in fulfilling rights. Where education is required to fulfill the 4A.